ACID-BASE EQUILIBRIA IN SOLUTIONS OF NEW 4-HYDROXYSTYRYL DYES BASED ON 1-OCTILPIRIDINIUM - A. N. Chebotarev; Yu. P. Zhukova; Ya. I. Studenyak; D. V. Snigur (Vìsnik Odesʹkogo Nacìonalʹnogo Unìversitetu: Hìmìâ, 2019)
In this paper, the acid-base properties of a number of new 4-hydroxystyryl dyes based on 1-octylpyridinium in solutions have been studied by tristimulus colorimetry and spectrophotometry. The studied dyes are obtained by the interaction of equivalent amounts of corresponding heterocyclic methylene bases salts with 4-hydroxyaldehydes in acetonitrile. The advantages of the tristimulus colorimetric method in the study of acid-base equilibria in dyes solutions were noted. It was shown that the use of data on the change in the values of colorimetric functions (specific color discrimination), depending on the medium acidity allows us to determine the constants of ionization of the functional groups of 4-hydroxystyryl dyes. It was shown that the quantitative description of the color of objects of different nature by calculating their color coordinates on the basis of spectrophotometric data allows obtaining information about their state in solutions. Using the values of the colorimetric functions of the ionic-molecular forms of 4-hydroxystyryl dyes as an analytical signal allows us to obtain a coherent picture of existing acid-base equilibria in a wide range of the medium acidity. Based on the obtained experimental data, a probable scheme of acid-base equilibrium in aqueous solutions of 4-hydroxystyryl dyes was proposed. It was shown that in the acidic medium 4-hydroxystyryl dyes exist in a protonated single-charged cationic form, and with pH rise dissociation of phenolic hydroxyl and tautomerization with the formation of a merocyanine form occurs. The corresponding diagrams for the distribution of ion-molecular forms of 4-hydroxystyryl dyes have been constructed, depending on the acidity of the medium.